Faktor-Faktor yang Mempengaruhi Motivasi Pekerja pada Proyek Konstruksi Berdasarkan Latar Belakang Pekerja - Andhika Pradikta Setiawan; Anton Soekiman (Rekayasa Sipil, 2023)
The benefits of motivation are that the work or task that is the responsibility of the worker will be completed quickly, worker absenteeism can be minimized, and the labor turnover will be smaller. Construction projects can absorb a lot of workers, each worker has a different background, different backgrounds can affect a person's mindset and interest differences, thus affecting the level of motivation and factors that can increase motivation will be different. This research is dedicated to find out what factors can affect the motivation of workers based on the background of workers. There are 30 factors that can increase the motivation of workers obtained from the literature review of previous research, which will be searched for its relationship with the level of motivation of workers by using regression analysis. A total of 212 respondents to obtain sample data to find the relationship of factors that can affect motivation with the level of motivation of workers using regression analysis. From the results of this study, it was found that the factors that have an influence on the motivation of workers in each classification of background, the result is that almost every different background has a different factor that has the most influence on the motivation of workers, so that everyone who has a different background has a different way of increasing motivation.